2011
DOI: 10.3758/s13428-011-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

A normative study of acronyms and acronym naming

Abstract: Acronyms are an idiosyncratic part of our everyday vocabulary. Research in word processing has used acronyms as a tool to answer fundamental questions such as the nature of the word superiority effect (WSE) or which is the best way to account for word-reading processes. In this study, acronym naming was assessed by looking at the influence that a number of variables known to affect mainstream word processing has had in acronym naming. The nature of the effect of these factors on acronym naming was examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 125 publications
(157 reference statements)
4
30
0
Order By: Relevance
“…AGE is a high-frequency word. These words are more easily recognized, produced and recalled faster and with greater accuracy than lowfrequency words or than a more complex newly generated acronym (Izura and Playfoot, 2012).…”
Section: Anticipated Gamete Exhaustion (Age)mentioning
confidence: 99%
“…AGE is a high-frequency word. These words are more easily recognized, produced and recalled faster and with greater accuracy than lowfrequency words or than a more complex newly generated acronym (Izura and Playfoot, 2012).…”
Section: Anticipated Gamete Exhaustion (Age)mentioning
confidence: 99%
“…However, while there is considerable evidence to suggest that familiar acronyms do have phonological representations in the lexicon much as words do (Brysbaert et al, 2009;Slattery et al, 2006) our recent work has indicated that these representations do not necessarily need to be accessed for a correct pronunciation to be reached (Izura & Playfoot, 2012;Playfoot, Izura & Tree, 2013). Instead, we have argued that acronym naming can be achieved through the application of a single sub-lexical rule.…”
mentioning
confidence: 78%
“…BBC or DVD). We have previously referred to this type of acronym as unambiguous (Izura & Playfoot, 2012) because it is immediately clear from the orthography of these items that naming each letter in turn is the only sensible way of generating a pronunciation. There are also acronyms that contain both vowels and consonants (e.g.…”
mentioning
confidence: 99%
See 2 more Smart Citations